Transforming human resource management with artificial intelligence: A systematic review and ethical framework for future HR practices - Rani, Geeta; Shokeen, Rita; Kataria, Himanshu; Dabas, Richa (The International tax journal, 2026)
Purpose: This study systematically explores the role of Artificial Intelligence (AI) in transforming Human Resource Management (HRM), with a focus on recruitment, employee engagement, and decision-making. It aims to consolidate fragmented research, address ethical issues, and highlight sector-specific AI applications in HR practices. Design/methodology/approach: A systematic literature review (SLR) was conducted. following the PRISMA framework to ensure methodological rigor and transparency. Seventy-five peer-reviewed studies published between January 2020 and May 2025 were examined using databases such as Scopus, Web of Science, IEEE Xplore, SpringerLink, and Google Scholar. Data were summarized through narrative and tabular mapping to compare traditional HR approaches with AI-powered methods. Findings: The review reveals that AI significantly enhances recruitment efficiency by reducing the time-to-hire by nearly 50%, increases employee engagement through real-time sentiment analysis, and improves HR decision-making with predictive analytics that achieve a turnover prediction accuracy of over 75%. However, issues such as data bias, privacy concerns, and employee resistance remain significant. Industry-specific uses reveal that AI adoption varies across technology, healthcare, retail, finance, and education, emphasizing the need for tailored implementation. Research limitations and implications: The study is restricted to peer-reviewed publications in English from 2020 to 2025.